Questioning locality: the UBC Museum of Anthropology and its hinterlands Questionando a localidade: o UBC Museum of Anthropology e os seus arredores - Anthony Shelton (Etnográfica: Revista do Centro em Rede de Investigação em Antropologia, 2007)
This paper argues that locality is itself a culturally constructed category which, if not critically assessed may hide the political relations existing between museums and other institutions within a specified museumscape. Frequently, museums, as in the case of British Columbia, operate at local, national and sometimes regional levels. While acknowledging the importance of studies on the poetics of museum exhibitions and display, critical museology cannot discount the political and historical contexts under which museums operate or omit analysis of the ideologies with which they are enshrouded. Este artigo defende que a "localidade" é uma categoria culturalmente construída que, não sendo discutida de forma crítica, poderá esconder as relações políticas entre os museus e as instituições num determinado cenário museológico. Tal como é o caso da British Columbia no Canadá, frequentemente os museus operam em registos locais, nacionais e por vezes regionais. Apesar de reconhecer a importância dos estudos sobre a poética das mostras museológicas, a museologia crítica não pode ignorar os contextos políticos e históricos onde os museus operam, nem omitir a análise das ideologias que os envolvem.